2021
DOI: 10.1371/journal.pone.0256871
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on clinical research in the UK: A multi-method qualitative case study

Abstract: Background Clinical research has been central to the global response to COVID-19, and the United Kingdom (UK), with its research system embedded within the National Health Service (NHS), has been singled out globally for the scale and speed of its COVID-19 research response. This paper explores the impacts of COVID-19 on clinical research in an NHS Trust and how the embedded research system was adapted and repurposed to support the COVID-19 response. Methods and findings Using a multi-method qualitative case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…The speed of clinical research and its publication have been unprecedented in several countries. 22 High-income North-American and Western European countries appear to have taken the lead in conducting research on Covid-19. 13 The research on the major co-morbidities related to Covid-19, such as diabetes, obesity, and hypertension, also appears to have been dominated by the same countries.…”
Section: Discussionmentioning
confidence: 99%
“…The speed of clinical research and its publication have been unprecedented in several countries. 22 High-income North-American and Western European countries appear to have taken the lead in conducting research on Covid-19. 13 The research on the major co-morbidities related to Covid-19, such as diabetes, obesity, and hypertension, also appears to have been dominated by the same countries.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of the United Kingdom’s research mobilization was in large part predicated on the pre-existing embeddedness of the clinical research system within the National Health Service (NHS), a public, free-at-point-of-delivery healthcare system. As we detail elsewhere, in addition to maintaining a routine level of service, hospitals have been tasked with delivering a high volume of emergency care alongside nationally prioritized COVID research, something which has required the large-scale reorganization of services, systems and working practices [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As of December 2021, over 265 million COVID-19 cases and more than 5 million associated deaths have been recorded worldwide [ 1 ]. The introduction of social distancing rules to curb the spread of the virus, staff redeployment to the intensive care unit, and prioritization of COVID-19 related research has not only resulted in a complete re-organization of hospital services but has also significantly impaired the conducting of clinical trials [ 2 ]. A study reviewing the ClinicalTrials.gov registry reported that 1052 trials were suspended, as a result of the pandemic, in 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%